Rectal cancer treatment locally advanced - Lussheimer, Daniel (Cirugía del Uruguay, 1994)
The objective of the treatment of the local/y advanced rectum cancer aims, in the first instance, at the reduction of the rate of locoregional recurrence, thereby prolonging the free interval of the disease, thus improving the quality of lite. This has been attained by preoperative radiotherapy. The possibility of combining effective chemiotherapy with we/1 controlled radiotherapy in prospective randomized schedules, offer a tempting potential designed to curtail the high mortality rate entailed by these patients by year 2000.